A Facility-based Family Support Intervention to Improve Treatment Outcomes for Adolescents on Antiretroviral Therapy in the Cape Metropole, South Africa. (November 2021) - Orth, Zaida; van Wyk, Brian
Adolescents living with human immunodeficiency virus (HIV) (ALHIV) globally, report worse treatment outcomes compared to adults and children on antiretroviral therapy (ART). We conducted a photovoice study with eighteen ALHIV to explore experiences and challenges of being on ART, and individual interviews with 5 health workers to describe the challenges in treating ALHIV. The facility implemented the Family club intervention to facilitate caregivers (parent/guardians) supporting ALHIV on treatment. The health workers revealed that " disclosing HIV status " to children was the biggest challenge for caregivers and health workers. Participating ALHIV reported that family support and having a positive mentality were instrumental for continued treatment adherence. However, disclosure of HIV status to friends remained a challenge due to pervasive community stigma. Treatment fatigue and side - effects were also barriers to adherence. Family support was instrumental in facilitating adherence support for ALHIV. However, this (intervention) should include peer support to improve positive mental well-being in ALHIV.